2016
DOI: 10.1097/spv.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Organ Prolapse Stage and the Relationship to Genital Hiatus and Perineal Body Measurements

Abstract: Objectives Describe the relationship between genital hiatus (GH) and perineal body (PB) measurements with increasing pelvic organ prolapse stage in a large cohort of women referred to Urogynecology clinic for pelvic floor disorders. Methods Retrospective chart review of all new patients seen in an academic Urogynecology clinic between 1/2007 and 9/2011. Data were extracted from a standardized intake form. All patients underwent a Pelvic Organ Prolapse Quantification (POPQ) exam. Descriptive statistics compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 12 publications
5
32
0
Order By: Relevance
“…The height of the perineal body in adult nulliparous women, according to the definition of the POP-Q system, ranges between 3.1-4.1 cm. 198,199 We therefore chose to include women with a perineal body height of <2cm in order to maximize the likelihood of the study subjects having anatomic defects of the perineum (34% had a perineal body height <1 cm and 66% less than 2 cm). The lack of nonblinded outcome assessment may have caused measurement bias.…”
Section: Selection Bias and Misclassificationmentioning
confidence: 99%
“…The height of the perineal body in adult nulliparous women, according to the definition of the POP-Q system, ranges between 3.1-4.1 cm. 198,199 We therefore chose to include women with a perineal body height of <2cm in order to maximize the likelihood of the study subjects having anatomic defects of the perineum (34% had a perineal body height <1 cm and 66% less than 2 cm). The lack of nonblinded outcome assessment may have caused measurement bias.…”
Section: Selection Bias and Misclassificationmentioning
confidence: 99%
“…Other studies correlating POP-Q PB and POP-Q GH with the presence of prolapse have also shown similarly that increasing stages of prolapse are associated with POP-Q GH, but not with POP-Q PB [16]. POPQ PB + GH have been shown to improve the prediction of levator injuries in women with incontinence and prolapse [17].…”
Section: Discussionmentioning
confidence: 86%
“…There is no consensus regarding the clinical role of these landmarks in the management of pelvic organ prolapse (POP). PB has poor association with prolapse stage, whereas larger GH seems to be linked with prolapse greater than stage three, possibly due to pelvic muscle injury . A GH of 3.75 cm or more appears to be associated with apical support loss .…”
Section: Introductionmentioning
confidence: 86%